2019
DOI: 10.3389/fmars.2019.00366
|View full text |Cite
|
Sign up to set email alerts
|

Folian-cv1 Is a Member of a Highly Acidic Phosphoprotein Class Derived From the Foliated Layer of the Eastern Oyster (Crassostrea virginica) Shell and Identified in Hemocytes and Mantle

Abstract: The proteins derived from the foliated shell layer of the oyster, Crassostrea virginica, are unusually acidic and highly phosphorylated. Here we report the identification of a gene encoding a member of this class of phosphoproteins that we collectively refer to as folian. Using an in silico approach, a virtual probe was constructed from an N-terminal sequence (DEADAGD) determined for a 48 kDa folian phosphoprotein and used to screen an oyster EST databank. A sequence that matched the N-terminus of the 48 kDa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 107 publications
(163 reference statements)
1
7
0
Order By: Relevance
“…The overall SDS-PAGE profiles in Figure 4 suggest that aspartic acid-rich proteins were the major components of the EDTA-soluble organic matrix in this study as is reported in other bivalves [ 40 , 55 ]. This implies that these proteins may also bind to calcium [ 55 ] and that they are intrinsically disordered proteins.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The overall SDS-PAGE profiles in Figure 4 suggest that aspartic acid-rich proteins were the major components of the EDTA-soluble organic matrix in this study as is reported in other bivalves [ 40 , 55 ]. This implies that these proteins may also bind to calcium [ 55 ] and that they are intrinsically disordered proteins.…”
Section: Resultssupporting
confidence: 78%
“…This indicates that CgSE, which is predominantly composed of Stains-all-stainable acidic proteins, was rich in aspartic acid. This is typical for proteins found in shells [ 40 , 52 ] and which may exhibit properties common to intrinsically disordered proteins [ 52 ]. Moreover, TFMS-treated CgSE showed no distinguishable bands; instead, a diffused and scaling smeared pattern from 20 kDa to >250 kDa appeared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, gigasin-6 isoforms X1 and X2, as well as dentin sialophosphoprotein-like, were upregulated in the conspecific cue-induced PL batch. Gigasin-6 and its isoforms have been reported as a component in the adult shell matrix in C. gigas [60,61], while our sequence homology search on dentin sialophosphoproteinlike showed close homology to folian-cv1 in C. viriginica [62]. Others were related to signal regulation processes such as calmodulin A (LOC105327998), Wnt inhibitory factor 1/EGF-like domain containing protein 2 (Wif-1) (LOC105335286), tyrosine-protein kinase receptor Tie (LOC105338560), beta-2 adrenergic receptor (LOC105336903), nuclear receptors (LOC105338842, LOC105345246), and FMFRamide receptor (LOC105343238).…”
Section: Postlarvaementioning
confidence: 58%
“…Additionally, the presence of endogenous WGA-binding sugar found on the larval foot and mantle, in the present study, further confirms one of the hypotheses of Vasquez et al (2014). Their hypothesis explains that, during exposure of pediveliger larvae with WGA lectin treatment, this lectin may have to bound to shell matrix glycoproteins in the internal organs and mucopolysaccharides on the foot of the larvae [ 50 , 52 , 53 , 54 , 55 ], and thus, somehow interfered with C. gigas larval settlement behavior [ 9 ]. Shell matrix proteins, which are made by the mantle, interact with each other or with polysaccharides or chitin to produce the shell framework [ 56 ].…”
Section: Discussionmentioning
confidence: 99%